Implementasi permainan tradisional lombok dalam meningkatkan kebugaran jasmani - Kurniawan, Edi (Jurnal Porkes, 2023)
The purpose of this study was to examine the implementation of traditional Lombok games in improving physical fitness in grade V elementary school students. This study used a quasi experimental design (pretest and posttest) research method, the research design used was a pre one group pretest-posttest design. The sampling technique in this study was simple random sampling. The number of samples used in this study were 33 fifth grade students with an age of 10 years. This research instrument uses TKJI before and after implementation. The results of the pretest physical fitness assessment average value of 12 with a physical fitness category of less, while the posttest average value of 17 with a moderate physical fitness category, the results of data analysis from the study showed the output of the independent samples test, obtained a value of Sig. (2-tailed) = 0.000 <0.05. So the traditional Lombok game for grade V students aged 10 years has significant implementation benefits. Based on these results, it is concluded that it can show the importance of the implementation of traditional Lombok games which can provide benefits to improve proper physical fitness in later life.